2019
DOI: 10.1097/ju.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Implicated in Lower Urinary Tract Symptoms: Systematic Review and Pathway Analyses

Abstract: Purpose: Lower urinary tract symptoms are prevalent and burdensome, yet methods to enhance diagnosis and appropriately guide therapies are lacking. We systematically reviewed the literature for human studies of biomarkers associated with lower urinary tract symptoms. Materials and Methods: PubMedÒ, EMBASEÒ and Web of ScienceÒ were searched from inception to February 13, 2018. Articles were included if they were in English, performed in benign urological populations without neurological disorders or interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…Again, many studies have identified inflammatory pathways that contribute to female LUTS, including another pathway analysis specifically focused on overactive bladder where the majority of data came from female subjects. 13 While the proteins and pathways identified in this study implicate a role for inflammation and tissue growth in LUTS, they do not imply causation. If validated as biomarkers, future studies specifically evaluating their role in LUTS should be performed.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Again, many studies have identified inflammatory pathways that contribute to female LUTS, including another pathway analysis specifically focused on overactive bladder where the majority of data came from female subjects. 13 While the proteins and pathways identified in this study implicate a role for inflammation and tissue growth in LUTS, they do not imply causation. If validated as biomarkers, future studies specifically evaluating their role in LUTS should be performed.…”
Section: Discussionmentioning
confidence: 60%
“…However, many of these are cross-sectional association studies and demonstrate conflicting results. 13 Similarly, proteomic studies conducted in humans and animals with bladder outlet obstruction have identified several candidate proteins that may be differentially expressed, including optineurin, thioredoxin, preprohaptoglobin, and Kallikrein-Related Peptidase 2 (KLK2). 20 However, the results of these studies have not been reproduced and, therefore, require further validation; future studies that use panels of biomarkers and can be rigorously validated will be extremely important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring the urinary levels of IL-5 and ATP and entering their creatinine-normalised values, in addition to age and gender, in to the formula, the possibility of an individual being in the identified high OAB symptomatic score group could be predicted. This study provides the foundation for the development of novel non-invasive diagnostic tools for OAB, where the effects of biomarkers and key OAB confounders 31 could be considered in conjunction.…”
Section: Predictive Model Oab Prediction Equationmentioning
confidence: 99%
“…Anti brotic therapy may be an effective way to control bladder dysfunction, but it has not been well studied. [15][16][17] Fibronectin is an extracellular macromolecular membrane protein present on the surface of animal cells and is the main noncollagen glycoprotein in the ECM and basement membrane. It is also very abundant in the ECM of various tumors, including osteosarcoma, leiomyosarcoma, and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%